Analisis Program Gerakan Literasi Sekolah di Sekolah Dasar - Neng Wulan Anatasya; Prana Dwija Iswara (Lembaga Yasin AlSys, 2026)
Although the School Literacy Movement has become a national program to improve the reading and writing skills of elementary school students, studies that systematically map its implementation, impact, and challenges based on previous research still need to be strengthened. This study aims to examine the implementation, effects, and challenges of implementing the School Literacy Movement in elementary schools based on previous research findings. This study used a qualitative approach with a systematic literature review design. Data were collected through searches for relevant and high-quality national and international scientific articles published in the last ten years, then analyzed through thematic synthesis involving the stages of identification, selection, evaluation, and interpretation. The results show that the implementation of the School Literacy Movement has generally reached the habituation stage through fifteen-minute reading activities before learning, but the development and literacy learning stages have not been optimally implemented and have not been fully integrated into all subjects. The implementation of the School Literacy Movement has positive effects on increasing reading interest, independent learning, and students’ ability to search for, understand, and process information. The conclusion of this study affirms that the effectiveness of the School Literacy Movement in elementary schools requires strengthening the integration of literacy into learning, collaboration among teachers, parents, and librarians, and the sustainable use of educational technology. These findings imply the importance of developing school literacy strategies that are more systematic, collaborative, and adaptive to the learning needs of elementary school students.